3D Oleophilic Sorbent Films Based on Recycled Low-Density Polyethylene - Junaid Saleem (14670322) (2023)
Recycling low-end, one-time-use plastics—such as low-density polyethylene (LDPE)—is of paramount importance to combat plastic pollution and promote sustainability in the modern green economy. This study valorizes LDPE waste by transforming it into 3D oleophilic swellable thin films through a process involving dissolution, phase separation, and extraction. These films are subsequently layered using a customized polypropylene (PP) based nonwoven fabric separator and securely sealed in a zigzag pattern. The zigzag-shaped seal enhances the adhesion of pollutants to the sorbent by providing wire curvatures that increase retention time and uptake capacity. As a result, the sorbent exhibits impressive oil uptake capacities, with immediate and equilibrium values of 120 g/g and 85 g/g, respectively. Notably, the as-prepared sorbent demonstrates low water retention and high selectivity for oil, outperforming commercially available oil sorbents. The unique design involving a 3D-film structure, superposed films, and a zigzag-shaped seal offers a sustainable and value-added solution to the issues of LDPE waste and oil spills on water surfaces. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym16010135